2022
DOI: 10.51253/pafmj.v72isuppl-3.9553
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Respiratory Complications in Post COVID-19 Patients After Coronary Artery Bypass Grafting

Abstract: Objective: To determine the frequency of post-operative pulmonary complications after (coronary artery bypass grafting)CABG surgery and to compare the respiratory complications of post COVID and comparison group Study Design: Analytical Cross- sectional study Study Place and Duration: Study was conducted in Adult Intensive Care Unit, Armed Forces Institute of Cardiology,Rawalpindi Pakistan, from Sep 2021 to Mar 2022. Methodology: 40 patients were selected, and divided into two groups using N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…In a study conducted by Gabryel et al[ 14 ] on 444 lung cancer cases, 72 patients with a history of COVID-19 were compared with 372 patients without infection in terms of postoperative complications, and no significant differences were found. The research article methodologically closest to our study was reported by Shah et al[ 15 ] In this study, 20 patients with a history of COVID-19 infection and 20 patients without COVID-19 infection history were randomized, and pulmonary complications after cardiac surgery were compared. The study reported a higher incidence of pulmonary complications in the group with a history of COVID-19, longer intensive care unit stay, and a higher frequency of noninvasive mechanical ventilation in patients with a medical history of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…In a study conducted by Gabryel et al[ 14 ] on 444 lung cancer cases, 72 patients with a history of COVID-19 were compared with 372 patients without infection in terms of postoperative complications, and no significant differences were found. The research article methodologically closest to our study was reported by Shah et al[ 15 ] In this study, 20 patients with a history of COVID-19 infection and 20 patients without COVID-19 infection history were randomized, and pulmonary complications after cardiac surgery were compared. The study reported a higher incidence of pulmonary complications in the group with a history of COVID-19, longer intensive care unit stay, and a higher frequency of noninvasive mechanical ventilation in patients with a medical history of COVID-19.…”
Section: Discussionmentioning
confidence: 97%